PENGGUNAAN MANIK-MANIK SEBAGAI ALAT PERAGA SEDERHANA DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA KELAS XII IPA PADA KONSEP DNA DI SMA NEGERI 4 TANAH JAMBO AYE KABUPATEN ACEH UTARA - Fadhli Nirwansyah (Universitas Islam Negeri Ar-Raniry, 2015)
A classroom action research entitledâ€œThe use of beads as simple propsas an effort to improvethe achievement of studentsClass XII Science at SMAN 4 Tanah Jambo Aye, Aceh Utara regencyon the concept of DNAâ€ has been conducted in the first semester of the school year 2014/2015. The research aims to find out the effect of the use of beads as simple props as an effort to improve the achievement of studentsclass XII Scienceat SMA 4Tanah Jambo Aye Aceh Utara districton the concept of DNA The method used was classroom action research (PTK), which consisted of 2 cycles. The subject of this research was 30 students of class XII,science (IPA1) of SMAN 4 Tanah Jambo Aye in odd semester academic year 2014/2015.The data were analyzed by using comparative descriptive analysis techniques by comparing the initial conditions with the results achieved from each cycles and using qualitative descriptive analysis by comparing the results of observations and reflection on the first cycle and the second cycle. The results showed that the use of beads as simple props can improve the achievement of students class XII Science of SMA 4Tanah Jambo Aye, Aceh Utara district on DNA material. It can be seen fromthe improvement of studentsâ€™ mastery learning in the first cycle was 66.67%, while the second cycle was 93.33%.